Ninety Ampere Welding Produced Superior Dissimilar Metal Joint Performance: Pengelasan 90 Ampere Menghasilkan Kinerja Sambungan Logam Berbeda yang Unggul - Septian, Dhimas Wahyu Dwi; Mulyadi (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Dissimilar metal welding is widely used in industrial applications where different materials are combined to balance mechanical strength, corrosion resistance, and economic efficiency. Specific Background: Carbon steel ASTM A36 provides good strength and low cost, while stainless steel 316 offers superior corrosion resistance, making their combination attractive for structural applications. Knowledge Gap: Although dissimilar metal welding has been widely studied, limited experimental data directly compare the effects of welding current and cooling media on tensile properties and macrostructure in ASTM A36 and stainless steel 316 joints using stainless steel electrodes. Aims: This study aims to analyze the effect of welding current and cooling conditions on the tensile strength and macrostructure of dissimilar metal welded joints. Results: Nine specimens were welded using current variations of 70 A, 80 A, and 90 A with air, natural air, and oil cooling. The highest stress value was 389.060 Kgf/mm² at 90 A with oil cooling, the highest strain value was 0.039 at 90 A with oil cooling, and the highest elastic modulus was 11,610 Kgf/mm² at 90 A with natural air cooling. Macrostructure observation showed that the 90 A natural air specimen had no visible welding defects, while the 70 A water-cooled specimen showed porosity, underfill, arc strike, and slag inclusion. Novelty: The study directly compares current variation and cooling media simultaneously in dissimilar metal welding between ASTM A36 and stainless steel 316. Implications: Proper current selection contributes to better tensile performance and improved weld quality in dissimilar metal joining applications. Keywords: Dissimilar Metal Welding, Welding Current, Tensile Strength, Macrostructure, ASTM A3 Key Findings Highlights The 90 A parameter produced the most favorable overall mechanical response. Defect-free weld morphology appeared under natural air cooling at high current. Lower current generated more visible discontinuities in the welded region.